Potentials and challenges of agile project management in real estate development - Klarissa Klotschke; Benjamin Wagner; Andreas Pfnür (Technische Universität Darmstadt, Forschungscenter Betriebliche Immobilienwirtschaft, 2022)
Managing changing requirements and complexity is important in enhancing the success of real estate projects. Agile project management provides approaches for adapting processes and working methods accordingly. This study aims to identify the potentials and challenges of agile project management in real estate development. Therefore, a literature analysis placed principles and methods of agile project management in the context of real estate project management. These perceptions were verified with qualitative content analysis based on semi-structured interviews. The main potentials arise through the integration of the occupier as key customer and the consideration of his or her needs through an iterative approach. In connection, incremental planning has the potential to reduce uncertain requirements and facilitate creative solutions. Self-organised teams offer the possibility to improve cooperation between interdisciplinary teams and the sense of responsibility, even if the lack of hierarchy is considered a challenge by the experts. Due to strong conflicts of interest, regulations and expensive, complex product adjustments, challenges and limitations of the approaches are seen. These results provide insights on where agile project management can help real estate project management with the current complexities, but also how it needs to be adapted for widespread application in real estate development.
Keywords: 650; agile project management; real estate development; agility; real estatetransformation